Microsporidial stromal keratitis: characterisation of clinical features, ultrastructural study by electron microscopy and efficacy of different surgical modalities. Issue 11 (12th February 2020) - Huang, Hsin-Yu; Wu, Cheng-Lin; Lin, Sheng-Hsiang; Lin, Wei-Chen; Huang, Fu-Chin; Hung, Jia-Horung; Tseng, Sung-Huei
Abstract : Aims: To report the clinical manifestations, ultrastructure and evaluate the efficacy of therapeutic lamellar keratectomy (TLK) and penetrating keratoplasty (PK) for microsporidial stromal keratitis (MSK). Methods: Fourteen MSK cases between 2009 and 2018 were recruited. Each patient's clinical presentation, light microscopy, histopathology, PCR and electron microscopy (EM) of corneal samples were reviewed. Results: The patients were 70.0±4.7 years old (average follow-up, 4.5 years). Time from symptoms to presentation was 10.6±13.0 weeks. The corneal manifestations were highly variable. Corneal scrapings revealed Gram stain positivity in 12 cases (85.7%) and modified Ziehl-Neelsen stain positivity in 9 (64.3%). Histopathology revealed spores in all specimens, while sequencing of small subunit rRNA-based PCR products identified Vittaforma corneae in 82% of patients. EM demonstrated various forms of microsporidial sporoplasm in corneal keratocytes. All patients were treated with topical antimicrobial agents or combined with oral antiparasitic medications for >3 weeks. As all patients were refractory to medical therapy, they ultimately underwent surgical intervention (TLK in 7, PK in 6 and 1 received TLK first, followed by PK). Postoperatively, the infection was resolved in 78.6% of the patients. Nevertheless, a high recurrence rate (21.4%) was noted during 3-year follow-up, with only two patients retained a final visual acuity ≥20/100. Conclusion: MSK usually presents with a non-specific corneal infiltration refractory to antimicrobial therapy. The diagnosis relies on light microscopic examinations on corneal scrapings and histopathological analyses. Surgical intervention is warranted by limiting the infection; however, it was associated with an overall poor outcome.